Musculoskeletal adaptation of young and older adults in response to challenging surface conditions. (November 2022) - Holcomb, Amy E.; Hunt, Nicholas L.; Ivy, Amanda K.; Cormier, Aidan G.; Brown, Tyler N.; Fitzpatrick, Clare K.
Abstract: Over 36 million adults over 65 years of age experience accidental falls each year. The underlying neuromechanics (whole-body function) and driving forces behind accidental falls, as well as the effects of aging on the ability of the musculoskeletal system to adapt, are poorly understood. We evaluated differences in kinematics (lower extremity joint angles and range of motion), kinetics (ground reaction force), and electromyography (muscle co-contraction), due to changes in surface conditions during gait in 14 older adults with a history of falling and 14 young adults. We investigated the impact of challenging surfaces on musculoskeletal adaptation and compared the mechanisms of adaptation between age-groups. Older adults displayed greater hip and knee flexion and range of motion during gait, reduced initial vertical loading, and 13 % greater knee muscle co-contraction during early stance compared to young adults. Across age groups, the presence of an uneven challenging surface increased lower-limb flexion compared to an even surface. On a slick surface, older adults displayed 30 % greater ankle muscle co-contraction during early stance as compared to young adults. Older adults respond to challenging surfaces differently than their younger counterparts, employing greater flexion during early stance. This study underscores the need for determining lower-limb musculoskeletal adaptation strategies during gait and assessing how these strategies change with age, risk of accidental falls, and environmental surfaces to reduce the risk of accidental falls.